Analysis of the Influence of Employee Performance on the Success of Cow Milk Production at UPT PT HMT Batu - Ibrahim, Affan Hafizh; Kusumastuti, Anie Eka (CV. Komunitas Dunia Peternakan, 2025)
The performance of UPT PT HMT Batu employees plays a vital role in achieving successful cow milk production. Because whether a company is successful or not is greatly influenced by the performance of its human resources. UPT PT HMT Batu will not be able to run well if it does not have employees who can carry out their duties well. The time and location of the research were carried out from 6 – 27 November 2023 at UPT PT HMT Batu. The research method used is a mixture or combination of quantitative and qualitative methods in one study. The data collection technique was carried out using a Likert scale questionnaire given deliberately to 30 respondents selected using purpose sampling who were UPT PT HMT Batu employees. Research data was analyzed using multiple linear analyses to determine the relationship between the independent and dependent variables. The research results show that the independent variables, namely work quality, time discipline, and work experience, influence the success of cow's milk production, and the workload and working hours variables do not significantly influence.